2002
DOI: 10.2134/agronj2002.8700
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature–Tolerant Bradyrhizobium japonicum Strains Allowing Improved Soybean Yield in Short‐Season Areas

Abstract: In short‐season soybean [Glycine max (L.) Merr.] production areas, low soil temperature is potentially an important factor limiting soybean growth and yield. Some strains originating from cooler areas can cause more nodulation and nitrogenase activity under low‐temperature conditions. We have attempted to find Bradyrhizobium japonicum strains that can fix more N than strain 532 C under low‐temperature conditions. We selected 40 B. japonicum strains from the USDA collection based on their isolation from soils o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Therefore, morphological, biochemical and symbiotic characterization on selective medium seem to be more adequate. Successful nodulation and N 2 fixation in the Legume-Rhizobium symbiosis require a close compatibility between the two partners and appropriate soil environment (Hirsch et al, 2003;Leibovitch et al, 2001;Zhang et al, 2002;Mishra et al, 2012). Although rhizobia from four crop legumes have been characterized and have shown efficiency in increasing the host plants yield in the Guinea-Savannah zone of Cameroon (Ngakou et al, 2009), nothing is known about the similarities/differences between rhizobia symbionts of food crop legumes and those of tree legumes such as acacia species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, morphological, biochemical and symbiotic characterization on selective medium seem to be more adequate. Successful nodulation and N 2 fixation in the Legume-Rhizobium symbiosis require a close compatibility between the two partners and appropriate soil environment (Hirsch et al, 2003;Leibovitch et al, 2001;Zhang et al, 2002;Mishra et al, 2012). Although rhizobia from four crop legumes have been characterized and have shown efficiency in increasing the host plants yield in the Guinea-Savannah zone of Cameroon (Ngakou et al, 2009), nothing is known about the similarities/differences between rhizobia symbionts of food crop legumes and those of tree legumes such as acacia species.…”
Section: Introductionmentioning
confidence: 99%
“…P is an essential element for cell division, root development and seed formation (Gizawy and Mehasen, 2009). Similarly, Zhang et al (2002) reported that B. japonicum bacteria application increased the number of seed per plant of two soybean cultivars.…”
Section: Number Of Seed Per Plantmentioning
confidence: 88%
“…Olivera et al (2002) declared that the effect of combined inoculation of bean by phosphate solubilizing bacteria and Bradyrhizobium japonicum bacteria were positive on dry weight. Moreover, Zhang et al (2002) reported that B. japonicum bacteria increased number of pods per plant, number of seeds per plant, hundred seed weight, grain protein, total protein and development of plant leaves in two soybean cultivars. Kazemi et al (2005) also stated that soybean seed inoculation by rhizobial bacteria significantly increased the number of pods per plant, number of seeds per plant, thousand grain weights and finally the yield of soybean.…”
Section: Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Nodulation and N 2 fixation in symbiosis require that host and microorganism are compatible, but also that the soil environment be appropriate for the exchange of signals that precede infection (Hirsch et al, 2003;Leibovitch et al, 2001;Zhang et al, 2002). Furthermore, microbial communities are able to develop a range of activities that are very important in maintaining biological balance and sustainability in soil particularly under stress conditions Kennedy and Smith, 1995).…”
Section: Physio-biochemical Characterizationmentioning
confidence: 99%